天氣系統與太空天氣交互作用 - 林建宏; 蕭棟元; 劉正彥 (2013)
計畫編號:NSC100-2628-M006-002-MY3 執行機構:國立成功大學地球科學系 研究期間:2013-08~2014-07 本計畫將研究電離層電漿結構受到低層大氣天氣系統所產生的大氣潮汐影響，近年 研究發現，低層大氣天氣系統中的赤道旺盛對流系統(tropical convection)以及高緯度平 流層瞬間增溫(stratosphere sudden warming, SSW)現象會產生向太空傳播的大氣潮汐， 這些大氣潮汐可能傳播到電離層E 層並影響電離的發電效應，進而影響低緯度地區的 赤道異常電漿結構，使得電離層F 層的電漿結構產生沿經度方向的變化以及其他的異 常變化。本計畫將研究大氣對流系統如何將其產生不同模式的大氣潮汐傳播到不同高 度的電離層，以及哪一個模式的大氣潮汐對電離層電漿的影響較具有貢獻。此外，近 年發現高緯度平流層瞬間增溫時期，低緯度的電離層電漿結構同時產生異常變化，研 究高緯度的低層大氣現象如何傳播到低緯度電離層是目前重要且被重視的研究題目。 除了研究電離層電漿結構如何受到大氣系統的影響之外，本計畫也將研究大氣潮汐效 應產生的擾動是否因為擾動電離層底部使得Rayleigh-Taylor Instability 較容易觸發，進 而產生有利於電漿泡的生成的條件。 The proposal will study the lower atmosphere meteorological weather effect to the ionospheric plasma structure. Recent studies show that the equatorial ionospheric plasma is affected by the upward propagating tides originated from deep tropical convection and the high latitude. stratosphere sudden warming effect. The upward propagating tides may propagate to the E region of the ionosphere and modulate the ionospheric dynamo, leading to plasma structure variations at the low latitude ionosphere. This proposal will study the characteristics of various modes of the nonmigrating tides and their effects in modulating the ionospheric dynamo process. At the mean time, we will also study the stratospheric sudden warming effect to the ionospheric plasma structure. Finding out how the meteorological effect occurring around arctic may affect the low-latitude ionospheric plasma is a crucial and important topic in the atmosphere-ionosphere coupling study. On the other hand, the abovementioned meteorological effects may produce wares to reach the bottom side ionosphere providing a condition where the Rayleigh- Taylor instability occurs easier and results in plasma bubbles.